Robert Ludlum's The Bourne objective : a new Jason Bourne novel - Lustbader, Eric.; Ludlum, Robert, 1927-2001. (London : Orion, 2010)
Jason Bourne, nearly killed in an ambush in Indonesia, assumes a new identity and recommences his quest to learn who he really is, but when an American passenger jet is shot down over Egypt by what appears to be an Iranian missile, he joins a global team, led by Soraya Moore, to investigate the attack and possibly prevent another world war.
Adult.
Keywords: Aircraft accidents -- Fiction; Attempted assassination -- Fiction; Bombings -- Fiction; Bourne, Jason (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Aircraft accidents -- Fiction; Assassination -- Fiction; Bombings -- Fiction; Bourne, Jason (Fictional character) -- Fiction; Intelligence officers -- Fiction